Experimental study on the influence of background music on pedestrian movement in high densities - Zeng, Guang; Schadschneider, Andreas; Zhang, Jun; Song, Weiguo (Collective Dynamics, 2020)
It is interesting to investigate the effect of background music on pedestrian movement. This paper investigates the properties of crowd motion with external rhythms. With rhythm, pedestrians stop more frequently than without any rhythm. The stopping also increases with the increment of the tempo. Velocity and flow with rhythms are lower than that without any rhythm at high densities due to the more frequent stopping. Stepping behavior analysis shows that the step frequency with rhythms is smaller than that without any rhythm, especially at high densities. Dynamic coordinated behavior is weakened by music, which also affectsthe stepping behavior. Our study will be helpful for understanding the effect of background music on pedestrian movement.